A Taxonomic Revision of Axonopus P. Beauv. (Poaceae: Panicoideae) in India (Bangladesh Journal of Plant Taxonomy, 2024)
The status of the genus Axonopus P.Beauv. in India has been varyingly depicted by different workers so far. After comprehensive study, two species, namely A. compressus (Sw.) P. Beauv. and A. fissifolius (Raddi) Kuhlm., are justified for the country. The distributional incongruity of both species in India is unravelled here. The present record of A. fissifolius in Sikkim confirms its extended distribution to the Indian Eastern Himalaya. Additionally, this species is also reported for the first time from Meghalaya. Detailed descriptions of both species are appended here. Illustrations and photoplates, along with notes on habitat, phenology, and distribution, are also presented. A key to the Indian species of Axonopus is incorporated for correct identification and easy recognition.Bangladesh J. Plant Taxon. 31(1): 57-71, 2024 (June)